Potential Health Impact of Switching From Car to Public Transportation When Commuting to Work - Morabia, Alfredo (American Public Health Association, 2010)
We assessed humidity-corrected particulate matter (PM(2.5)) exposure and physical activity (using global positioning system monitors and diaries) among 18 people who commuted by car to Queens College, New York, New York, for 5 days, and then switched to commuting for the next 5 days via public transportation. The PM(2.5) differed little between car and public transportation commutes (1.41 μg/M(3)·min; P = .226). Commuting by public transportation rather than by car increased energy expenditure (+124 kcal/day; P < .001) equivalent to the loss of 1 pound of body fat per 6 weeks.